PENGEMBANGAN BUKU RAMAH CERNA DIGITAL UNTUK MENSTIMULASI KEMAMPUAN LITERASI ANAK USIA DINI - Rahma Cahyani, Esta; Pujiarto (Jurnal Tumbuh Kembang Anak Usia Dini, 2024)
This research aims to develop digital digest-friendly books to stimulate early childhood literacy skills. The developed book, titled "Blue Ball," is designed to be used by children aged 4-5 years. The research used the Research and Development (R&D) method with Borg and Gall procedures, through steps such as preliminary research, product format development, small-scale trial, and final revision. Data were collected through validation sheets, interviews, and observations. The research was conducted in five PAUD institutions in the East Sahu sub-district, with a sample of 10 students from TK Negeri 4 West Halmahera and PAUD Asri Lestari. The results of the assessment and validation showed that the book "Bola Biru" is very feasible to use as a learning medium to stimulate early childhood literacy skills. The Digital Digest-Friendly Book developed in this research focuses not only on technological aspects but also on content that is in accordance with early childhood development. The stories presented are designed to attract children's attention, increase interest in reading, and facilitate interactive literacy learning. By using a smartphone, the book provides a more practical and enjoyable learning experience for children. This research shows that the appropriate use of digital media can be an effective support tool for improving early childhood literacy skills.